Molecular determinants of cellular attachment-mediated zoonosis of emerging paramyxo- and arenaviruses. - Pryce, R (2018)
The spillover of viral pathogens from wild animal reservoirs into human populations is the predominant cause of emerging disease events worldwide and represents an acute and persistent threat to global health, economy, and biodefence. The ability of a virus to specifically attach to cell-surface receptors during host-cell entry is a critical determinant of cross-species transmission. Through crystallographic and biochemical analysis, this thesis presents a structural rationale for the determinants of differential host-cell receptor recognition, for paramyxo- and arenaviruses, two groups of important emerging viral pathogens. Comparative study of the protein architectures of cellular attachment-mediating glycoproteins from two non-pathogenic viral species—Whitewater Arroyo arenavirus (WWAV) and Cedar henipavirus (CedPV)—with those of highly pathogenic members within the same genera, provides a template for understanding the molecular basis of distinct receptor tropism characteristics. We demonstrate that the attachment glycoprotein of WWAV, whilst possessing a conserved overall fold, is highly diversified relative to pathogenic arenaviruses, despite the ability to recognise an overlapping repertoire of host-cell entry receptors. Whilst as yet poorly defined auxiliary receptors permit arenaviral entry into human cells in vitro, therefore not unequivocally precluding zoonosis of WWAV at the point of cellular attachment, primary receptor utilisation is a correlate of pathogenicity and therefore can account for the non-pathogenic nature of WWAV. In contrast, analysis of the attachment glycoprotein of CedPV reveals no such structural incompatibilities with established henipaviral entry receptors. Thus, these data support the hypothesis that zoonosis of CedPV is not restricted by cellular-attachment and, by extension, host cell attachment alone is insufficient to account for the severe pathogenesis of henipaviruses. The data and analyses presented herein provide a blueprint for the prediction of receptor tropism characteristics and therein assessment of the zoonotic potential of emerging viruses. Furthermore, in presenting a structure-based classification of the discrete structural states adopted by the conformationally labile arenaviral attachment glycoproteins, we provide a template for improved vaccine design.